A Review Of The Literature Of Quality And Performance Management - Reynold Pieter Jordan Vigeleyn Nikijuluw (Politeknik Negeri Ambon, 2017)
The meaning of quality and performance are different, however, they related in terms of management activity. In management, the existence of the two activities is unavoidable. Therefore, given the boundaries of success and failure is very thin. For these reason in-depth examination these terms and their relationship. In this paper we are going to discuss; strategic human resource management, the definition of quality and performance management, the History of Quality Management, Why quality and performance management, the purpose of quality and performance management, Quality and performance management principles, and performance appraisal.Quality,